Advances in Dependability Engineering of Complex Systems Proceedings of the Twelfth International Conference on Dependability and Complex Systems DepCoS-RELCOMEX, July 2 - 6, 2017, Brunów, Poland - Zamojski, Wojciech; Mazurkiewicz, Jacek; Sugier, Jarosław; Walkowiak, Tomasz; Kacprzyk, Janusz; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book gathers the proceedings of the 2017 DepCoS-RELCOMEX, an annual conference series that has been organized by the Department of Computer Engineering at the Faculty of Electronics, Wrocław University of Science and Technology, since 2006. Its mission is to continue the heritage of the other two cycles of events - the RELCOMEX conferences (1977-89) and Microcomputer Schools (1985-95) - so this year we can celebrate the 40th anniversary of its origins. In contrast to those preceding series, which were focused on conventional reliability analysis, the goal of DepCoS is to promote a more comprehensive approach to system performability, which is now commonly called dependability. This innovative research area provides answers to the latest challenges in reliability evaluation for contemporary complex systems. Its novelty is based on a multi-disciplinary approach to system theory, technology and maintenance of systems operating in real environments. Dependability analyses concentrate on the efficient completion of tasks, services and jobs by a system considered as a combination of technical, information and human assets, in contrast to "classical" reliability, which is generally limited to the analysis of technical resources and associated components and structures. The selection of papers for this volume illustrates the diversity of topics that need to be considered, from mathematical models and design methodologies through software engineering and data security issues, to practical engineering problems in technical systems. In addition, this edition of the conference hosted the 7th CrISS-DESSERT Workshop, which was devoted to the analysis and assurance of safety and cyber security in critical infrastructure and computer systems.
1.Detection of network attacks using hybrid ARIMA-GARCH model- 2.Towards mixed-mode risk management - a concept; Andrzej Bialas and Barbara Flisiuk -- 3.Software support of the Common Criteria vulnerability assessment -- 4.On the performance of some C# constructions -- 5.Deep Stacking Convex Neuro-Fuzzy System and its On-line Learning -- 6.Fault tolerant ASIC/ULA-based computing systems testing via FPGA prototyping with fault injection -- 7.Critical Energy Infrastructure Safety Assurance Strategies Considering Emergent Interaction Risk -- 8.Modelling an Optimal Capital Structure of the Telecommunication Company -- 9.Specification of constraints in a System-of-Systems configuration; Dariusz Caban and Tomasz Walkowiak -- 10.A Methodological Framework for Model-based Self-Management of Services and Components in Dependable Cyber-Physical Systems -- 11.Maintenance of wind turbine scheduling based on output power data and wind forecast -- 12.Deadlock detection in distributed systems using the IMDS formalism and Petri nets.- -- 13.Scheduling tasks in embedded systems based on NoC architecture using Simulated Annealing -- 14.Adaptation of Ant Colony Algorithm for CAD of complex systems with higher degree of dependability -- 15.Context-Aware Anomaly Detection in Embedded Systems;Fatemeh Ehsani-Besheli and Hamid R. Zarandi -- 16.Comparative analysis of calculations in cryptographic protocols using a combination of different bases of finite fields -- 17.Dynamic Redundancy in Communication Network of Air Traffic Management System -- 18.Availability models and maintenance strategies for smart building automation systems considering attacks on component vulnerabilities -- 19.Concept of multi-criteria evaluation of the airport security control process -- 20.Extending Continuous Integration with post-mortem debug automation of unhandled exceptions occurred in kernel or user mode applications -- 21.The Methodology of Studying of Active Traffic Management Module Self-Oscillation Regime -- 22.Effectiveness examination of a multi-channel CSMA/CA detector -- 23.IaaS vs. traditional hosting for web applications - cost effectiveness analysis for a local market -- 24.High quality stabilization of an inverted pendulum using the controller based on trigonometric function -- 25.The application of RFID technology in supporting the process of reliable identification of objects in video surveillance systems -- 26.Aspect-oriented management of service requests for assurance of high performance and dependability -- 27.Process of mobile application development from the security perspective -- 28.Managing and Enhancing Performance Benchmarks;Jakub Maleszewski and Janusz Sosnowski -- 29.Reliability Optimization for Controller Placement in Software-Defined Networks -- 30.Agent Approach to Network Systems Experimental Analysis in Case of Critical Situations -- 31.RELIABILITY ASSESSMENT OF DRIVING SYSTEMS OF CITY BUSES;Marek M³yñczak -- 32.Testing the significance of parameters of models estimating execution time of parallel program loops according to the Open MPI standard -- 33.On application of regime-switching models for short-term traffic flow forecasting -- 34.Critical information infrastructure protection model and methodology -- 35.The method of creating players in the marketing strategy;Henryk Piech -- 36.Principles of mobile walking robot control in scope of technical monitoring tasks -- 37.Computer Systems - Simple -- 38.Improving FPGA Implementations of BLAKE and BLAKE2 Algorithms with Memory Resources -- 39.Assurance Case Patterns On-line Catalogue;Monika Szczygielska and Aleksander Jarzêbowicz -- 40.Information system as a cause of cargo handling process disruption in intermodal terminal -- 42.Stability Enhancement Against Fluctuations in Complex Networks by Optimal Bandwidth Allocation -- 43.The scope of the collected data for a holistic risk assessment performance in the road freight transport companies -- 44.Language Processing Modelling Notation - orchestration of NLP microservices -- 45.Type Variety Principle and the Algorithm of Strategic Planning of Diversified Portfolio of Electricity Generation Sources.
Keywords: Computational intelligence; Artificial intelligence; Dynamics; Nonlinear theories; Computational Intelligence; Artificial Intelligence; Applied Dynamical Systems